EVALUATION ON THE PSO PROVISION FOR COMMUTER TRAINS THROUGH PERFORMANCE-BASED PLANNING TO IMPROVE THE SERVICE QUALITY OF ECONOMY-CLASS TRAINS - Budi Sitorus; Tulus Irfan Harsono Sitorus; Euis Saribanon (Institut Transportasi dan Logistik Trisakti, 2015)
Commuter train is one mode of transportation that get PSO aid from the government. The problems related to PSO, among others, are the absence of a common perception on the understanding/definition of PSO and yet all PSO activities are done through a tender process, different basic calculation on the required PSO fund among PSO-executing SOEs, no separation between PSO business activities and non-PSO business activities in the financial statement. In addition, the compensation given by the government for PSO assignment is not sufficient, so that the commuter train service faces many disruptions. For example, the matter of delay reflects that train is not reliable, rails and bridges are not in the prime condition, the signal has beenthe signal has been fade, overlow electric current (pantograph) is frequently disrupted.The purpose of this study is to know, understand and evaluate the provision of PSO in order to maximize the commuter train services. The benefit of this research is to contribute ideas related to the administration of PSO so that people can feel the benefits. The method used is qualitative approach, descriptive analysis, and evaluation on the policy of PSO provision. The results of this study are divided into: PSO provision for economy-class trains, commuter services in Jabodetabek, asserting the separation of service types, support for PSO service improvement, and performance-based planning concept.